União da raça : Frederico Baptista de Souza e a militância negra paulista no Brasil pós-abolição (1875-1960) - Tiéde, Lívia Maria, 1980- (2023)
Orientadores: Lucilene Reginaldo, Daniel Barros Domingues da Silva